2021
DOI: 10.1016/j.jmig.2020.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Gynecologic Cancers in Women after Uterine Artery Embolization

Abstract: Study Objective: To characterize the short-term incidence of gynecologic cancer after undergoing uterine artery embolization (UAE). Design: Retrospective cohort study. Setting: Commercial insurance claims database. Patients: Total of 15 393 United States women aged 18 to 64 years who underwent UAE between 2007 and 2017.Interventions: We used the IBM MarketScan (Armonk, NY) claims to identify adult women without previous gynecologic cancer diagnoses undergoing UAE between 2007 and 2017. Database queries identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Based on a recent A recent retrospective cohort study, who investigated the incidence of gynecologic cancers in adult females who had undergone UAE for fibroids between 2007 and 2017, the authors found that one in 497 women undergoing UAE was diagnosed with a gynecologic malignancy within 3 years after treatment and concluded that short-term malignancies after UAE highlight the importance of pre-procedure evaluation in symptomatic females and females with age-related risk. 45 Neither size, number, location, or type of fibroid represent a true contraindication of the procedure. [46][47][48][49] However, given the wide variations in the extent of fibroid disease, ranging from a single huge leiomyoma, numerous fibroids and those with a distinct anatomical location such as a pedunculated cervical fibroid, every case should be addressed individually.…”
Section: Bjrmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a recent A recent retrospective cohort study, who investigated the incidence of gynecologic cancers in adult females who had undergone UAE for fibroids between 2007 and 2017, the authors found that one in 497 women undergoing UAE was diagnosed with a gynecologic malignancy within 3 years after treatment and concluded that short-term malignancies after UAE highlight the importance of pre-procedure evaluation in symptomatic females and females with age-related risk. 45 Neither size, number, location, or type of fibroid represent a true contraindication of the procedure. [46][47][48][49] However, given the wide variations in the extent of fibroid disease, ranging from a single huge leiomyoma, numerous fibroids and those with a distinct anatomical location such as a pedunculated cervical fibroid, every case should be addressed individually.…”
Section: Bjrmentioning
confidence: 99%
“…Based on a recent A recent retrospective cohort study, who investigated the incidence of gynecologic cancers in adult females who had undergone UAE for fibroids between 2007 and 2017, the authors found that one in 497 women undergoing UAE was diagnosed with a gynecologic malignancy within 3 years after treatment and concluded that short-term malignancies after UAE highlight the importance of pre-procedure evaluation in symptomatic females and females with age-related risk. 45 …”
Section: Introductionmentioning
confidence: 99%
“… 90 Studies have estimated gynecologic cancer incidence after UFE to be 1 in 497 women in 3 years, which varied based on age. 46 , 88 , 89 , 91 …”
Section: The Evidence: Knowns and Unknownsmentioning
confidence: 99%